EFEKTIVITAS PENGGUNAAN AUDIO VISUAL PADA HASIL BELAJAR PENDIDIKAN AGAMA KRISTEN - Manullang, Epan (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2019)
Abstract - The research aim was to find out the using of audiovisual by teachers in learning Christian religious education of eight-grade of SMP Negeri 3 Parlilitan, Humbang Hasundutan in academic year 2018/2019. The research method was a quantitative descriptive. The result of the hypothesis test was obtained tcount=16,438 ttable=2,000 in the area of H0 rejection curve and acceptance of Ha. Thus the research hypothesis was accepted where the effectiveness of the using of audio-visual in learning outcomes of eight-grade SMP Negeri 3 Parlilitan in academic year 2018/2019 was higher than 75% of 100% expected. The achievement was 3,32 in the good category with a large percentage of 83,02% in the very strong category.Keywords: Audiovisual Media, Student Learning Outcomes